Protective effects of protocatechuic acid on retinal ganglion cells from oxidative damage induced by H2O2. (February 2015) - Wang, Zhuo; Pan, Xiaohong; Wang, Dan; Sun, Hongliu; Han, Fang; Lv, Changjun; Zhang, Xiuli
<x content-type="archive" xml:space="preserve">Abstract</x> Oxidative stress-induced retinal ganglion cell (RGC) death is one of the important factors in ocular disease such as glaucoma. The aim of this study is to investigate whether protocatechuic acid (PCA), a monomeric phenolic acid with strong free radical scavenging effects, could protect RGC from oxidative stress induced by H2O2 and provide a potential therapy drug. The viability of RGC was determined by the MTT reduction and lactate dehydrogenase (LDH) assay. The possible protective mechanism was investigated via detecting apoptosis by Hoechst staining, Bcl-2 and Bax protein levels by ELISA, caspase-3 activation and membrane potential by immunofluorescence, and caspase-3 mRNA expression by polymerase chain reaction (PCR) method. The results showed that PCA was effective in reducing apoptotic death induced by oxidative stress, mainly through inhibiting depolarization of membrane and activation of caspase-3, down-regulating of apoptosis-related protein Bax, and up-regulating Bcl-2.